2002
DOI: 10.1038/sj.onc.1205037
|View full text |Cite
|
Sign up to set email alerts
|

P53 mediates ceramide-induced apoptosis in SKN-SH cells

Abstract: Ceramide induces apoptotic cell death in a dose-and time-dependent manner in neuroblastoma SKN-SH cells. Pretreatment with caspase inhibitors blocks cell death, suggesting that a set of caspase activities including caspase 1, as well as caspase 3, are involved in ceramideinduced apoptosis in SKN-SH cells. Treatment with a caspase inhibitor 3 h after ceramide addition did not inhibit cell death, although caspase activity was substantially reduced. Ceramide-induced apoptosis is accompanied by accumulation of p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…Thus, it is plausible that an increase in SOD2 activity, as reported here (Table 3A) However, SOD2 overexpression has been correlated in different cancer cell types, including colorectal cancer cells, with suppression of neoplastic transformation, decreased proliferation in vitro, and reversion of malignant phenotype (51). Uncoupling of the electrochemical gradient by increased SOD2 activity can give rise to p53 up-regulation and induction of senescence in colorectal cancer cells (52), whereas p53-induced suppression of bcl-2 expression can activate the mechanism of cell death (53). Nevertheless, HT-29 cells have a mutated p53 (54); although it may be relevant in other models, a link between SOD2 and p53 in HT-29 cells is unlikely.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, it is plausible that an increase in SOD2 activity, as reported here (Table 3A) However, SOD2 overexpression has been correlated in different cancer cell types, including colorectal cancer cells, with suppression of neoplastic transformation, decreased proliferation in vitro, and reversion of malignant phenotype (51). Uncoupling of the electrochemical gradient by increased SOD2 activity can give rise to p53 up-regulation and induction of senescence in colorectal cancer cells (52), whereas p53-induced suppression of bcl-2 expression can activate the mechanism of cell death (53). Nevertheless, HT-29 cells have a mutated p53 (54); although it may be relevant in other models, a link between SOD2 and p53 in HT-29 cells is unlikely.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to its role in regulating neurite outgrowth, ceramide has been implicated as an inducer of apoptosis in a number of cell-types, including neuroblastoma cells (Tavarini et al 2000;Kim et al 2002). It could therefore be argued that the neurite-inhibiting effect of C 2 -ceramide is due to induction of cell-death.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the role of ERK in cell death is somewhat controversial, but it may be responsible for the signal-inducing apoptosis (Goillot et al, 1997;Mohr et al, 1998). Recent data showed that ERK activation-mediated anticancer drug Zn 2ϩ , peroxinitrate, and ceramide induced apoptosis in neuroblastoma SH-SY5Y cells, dopaminergic PC 12 cells, and astrocytes, respectively (Blazquez et al, 2000;Seo et al, 2001;Kim et al, 2002). We therefore next examined the expression of proteins in the MAPK pathway to assess which signal pathway relays the cell growth inhibition and/or induction of apoptosis signals.…”
Section: Discussionmentioning
confidence: 99%